Interest rate determinants in the Caribbean - Kendall, Patrick ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Seeks to identify the major determinants of lending rates within the region. Concludes that the level of deposit rates is the largest single determinant of lending rates.